1995
DOI: 10.1242/dev.121.7.2233
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mouse egg activation: presence of ryanodine receptors and effects of microinjected ryanodine and cyclic ADP ribose on uninseminated and inseminated eggs

Abstract: Sperm-induced activation of mammalian eggs is associated with a transient increase in Ca2+ concentrations thought to be derived from inositol 1,4,5-trisphosphate-sensitive and -insensitive intracellular stores. Whereas the importance of inositol 1,4,5-trisphosphate-sensitive Ca2+ stores has been evaluated, the identity and role of inositol 1,4,5-trisphosphate-insensitive stores are poorly understood. To explore the role of the ryanodine-sensitive Ca2+ store, we first used reverse transcription-polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…To the best of our current knowledge, at fertilization, Ca release appears to be mediated principally through IP 3 in mammalian eggs (Miyazaki et al, 1993). Although functional ryanodine receptors (Ayabe et al, 1995) and ryanodine-sensitive Ca stores (Swann, 1992) are present in mouse eggs, ryanodine receptor-mediated Ca release is not required for mouse egg activation Ayabe et al, 1995).…”
Section: Inositol 145-trisphosphatementioning
confidence: 95%
See 2 more Smart Citations
“…To the best of our current knowledge, at fertilization, Ca release appears to be mediated principally through IP 3 in mammalian eggs (Miyazaki et al, 1993). Although functional ryanodine receptors (Ayabe et al, 1995) and ryanodine-sensitive Ca stores (Swann, 1992) are present in mouse eggs, ryanodine receptor-mediated Ca release is not required for mouse egg activation Ayabe et al, 1995).…”
Section: Inositol 145-trisphosphatementioning
confidence: 95%
“…Direct and indirect localization studies of the distribution of Ca binding and regulatory proteins are consistent with their localization in the ER. These include the IP 3 receptor, a ryanodine receptor/ Ca release channel, calsequestrin and calreticulin (Henson et al, 1989(Henson et al, , 1990McPherson et al, 1992;Kume et al, 1993;Parys et al, 1994;Ayabe et al, 1995;Shiraishi et al, 1995). IP 3 induces Ca release principally from the ER in studies of oocyte cytoplasmic fractions (Han and Nuccitelli, 1990).…”
Section: Development Of Competence To Undergo Cg Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In ascidians, the IP3 receptor generates Ca 2+ release responsible for the fertilization-associated Ca 2+ wave, but Ca 2+ released through the ryanodine receptor promotes post-fertilization plasma membrane insertion events that do not occur when only the IP3 receptor is active [157]. Although the ryanodine receptor can be detected in mammalian eggs, it does not appear to contribute significantly to Ca 2+ release or other egg activation events at fertilization in mammals [158][159][160][161].…”
Section: Ip3 Receptormentioning
confidence: 99%
“…There is little doubt that IP 3sensitive stores are present in oocytes (Miyazaki et al, 1993;Kline and Kline, 1994;Fissore et al, 1995;Miyazaki, 1995). On the other hand, ryanodine-sensitive stores have been detected by some workers (Swann, 1992;Ayabe et al, 1995;Yue et al, 1995;Sousa et al, 1996a) but not by others (Miyazaki et al, 1993;Kline and Kline, 1994;Fissore et al, 1995). The presence of ryanodinesensitive calcium stores in oocytes and their role in the oocyte activation mechanism have been recently demonstrated in humans (Sousa et al, 1996a), and these calcium stores have been suggested to participate, together with IP 3 -sensitive stores, in a two-store mechanism of calcium oscillations Tesarik and Sousa, 1996).…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%